UNITED NATIONS DEVELOPMENT PROGRAMME (UNDP) AGRICULTURAL INTERVENTION THROUGH MICRO-FINANCE AND POVERTY ALLEVATION IN UYO METROPOLIS, AKWA IBOM STATE, NIGERIA. - Amokeye, Adalikwu, Rose; Offiong M., Isa; Beauty, Usoroh, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The study assessed United Nations Development Programme (UNDP) micro-finance service andpoverty alleviation in Uyo local government area of Akwa Ibom State, Nigeria. It determined microcredit programme, increase income of farmers and improvement in farmers’ status as they relateto poverty alleviation. Survey research design was adopted and was conducted in 4 clans of studyarea. Eight villages within these strata were purposively studied on the basis of micro creditbeneficiaries. Altogether 240 rural farmers were involved. Data were obtained usingquestionnaire and analyzed using Pearson product moment correlation coefficient. Findingsshowed that average income of farmers increased after participation in UNDP micro-financeservice. It was established that farmers experience improvement in their social status. Therefore,participating in the UNDP programme has a positive impact in farmers’ income level and